Practice Architecture in Community Development: Mapping Traditions in Learning and Action - Bernhard, Michael; Van Daele, Christa (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2023)
This paper investigates a trajectory of 40 years of evolving practices in grassroots community development at an organization in southwestern Ontario. By drawing on this example, we present fresh perspectives in socially transformative ways of knowing and discovering. In doing so, we aim to elucidate traditions in adult education and community development that have flown under the radar. Our analysis is based on qualitative content analysis of written sources. Taking a practice theory perspective, we explore practice architectures as the cultural‑discursive, material‑economic, and social‑political arrangements that enable or constrain the learning of and participation in particular practices that contribute to social innovation. Our findings suggest that the application of a practice theory framework to the complex and often unarticulated work of community development aids in bringing to light the creative ways in which the associated practices emerge, get shaped, and get acquired. We posit that day‑to‑day practices can be aligned with deeper perspectives and adapted to changing conditions, rather than aligned with a narrow search for best practices.